The climate regime as global forest governance: can reduced emissions from Deforestation and Forest Degradation (REDD) initiatives pass a dual effectiveness test?. (1st September 2008) - Levin, K; McDermott, C; Cashore, B
For two generations, policy makers, environmental groups, industry associations and other stakeholders have given global forest deterioration concerted and sustained attention. Widespread disappointment over the failure to achieve a binding global forest convention at the 1992 Rio Earth Summit has been followed by frustration over the relatively limited impact to date of post-Rio forest-related global policy initiatives, including intergovernmental and non-state efforts. This paper argues that reduced emissions from deforestation and forest degradation (REDD) initiatives will yield significant impacts only if decision makers are committed to a results-based dual effectiveness test, addressing both forest degradation and global emissions reductions, and involving significant and measurable global-scale targets. While the importance of such a commitment may appear obvious, lessons from past forest and climate efforts suggest that greater results-based accountability is needed to overcome short-term and narrowly defined organizational and national self-interest.